The Management Of Rural Development And The Improvement Of The Potential Of Local Community Prosperity In Cimanggis Village , Bojonggede Sub District, Bogor Regency West Java Province - Marislinda Idris; Baharuddin Baharuddin; Donna Sampaleng (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2018)
The results and the evaluation of this community services is to explain the Management of Rural development and the Improvement of Local Potency-Based Community Prosperity in Cimanggis village, Bojonggede sub-district, Bogor regency, East Java Province. A qualitative approach with a SWOT analysis was employed. The results and the evaluation of this community services was to understand and explain what strategy is suitably adopted by the government of Cimanggis village in managing the rural development and the improvement of the community prosperity based on the local potency in Cimanggis village, Bojonggede sub-district, Bogor regency, East Java province. A defensive strategy was adopted by making use of and optimizing the attitude of village government in persuading the people to be willing to manage the rural development in line with the potency of the village. The authors found the following driving factors namely: 1) the attitude of the village government in persuading the people to do the rural development; 2) the village fund which was supporting and which is suitable with the target; 3) the gotong royong (mutual cooperation) culture; 4) the implementation of the rural development which was in line with village potency. Meanwhile the inhibiting factors were as follows: 1) the people’s mindset which still needed a good understanding and approach 2) the fence between the houses which hindered the road development; 3) the climate which was often changing; and 4) less responses from the heads of RTs (administrative village which is the lowest level of government administration) in informing activities to the people.